RELEVANSI HUKUM DAN HAK ASASI MANUSIA DENGAN AGENDA REFORMASI: DIMENSI NASIONAL DAN INTERNASIONAL - Ismail Marzuki; Faridy Faridy (STIH Putri Maharaja, 2020)
In life, humans certainly cannot be separated from their social interactions with others. Friction between individuals or between nations is something that is inevitable. That is because the understanding of the legal system and culture of a different society. The difference in opinion certainly needs to be harmonized by not locking up the meeting room of everyone's expression. From here, the existence of legal rules/norms on the one hand becomes important in people's lives. On the other hand, the recognition, respect and protection of human rights are also important to be accommodated. Therefore, this article examines the law as a means of maintaining social order, and human rights as a set of rights that describe the existence of human freedom in expressing their actions, and how relevant they are to the reform agenda, namely enforcing the law against violators of human rights seriously, both in national and international.